Development and testing of a patient‐derived questionnaire for treatment of neovascular age‐related macular degeneration: dimensions of importance in treatment of neovascular age‐related macular degeneration. Issue 8 (9th September 2018) - Jelin, Elma; Wisløff, Torbjørn; Moe, Morten C.; Heiberg, Turid
Abstract: Purpose: Studies reporting on patient perspectives during treatment of neovascular age‐related macular degeneration (nAMD) are limited. Thus, the aim of this study was to develop and test psychometric performance of a patient‐derived questionnaire to capture important experiences during intravitreal treatment. Methods: Patients ( n = 44) with at least 3‐month experience of intravitreal injection treatment for nAMD identified the dimensions of priority and also performed a weighting procedure to develop a score for comparison. The questionnaire comprised two versions: one focusing on the relative importance' of the dimensions and one on the experience of the 'management' during treatment. The questionnaire was then tested for psychometric performance in a longitudinal design in newly diagnosed patients at baseline ( n = 197), after three ( n = 184) and six ( n = 150) months of treatment. Results: Of the 15 included dimensions, the following were most frequently reported: 'receive treatment to preserve vision', 'information', 'waiting time', 'trust' and 'accommodating staff. The psychometric testing showed moderate reliability (intraclass correlation coefficient: 0.65–0.67) for the two versions and high level of face validity (8.3). The dimensions, 'preserving vision', 'early access to treatment', 'pain relief', 'information about the treatment/diagnosis' and 'visual aids' were consistently reported higher in 'importance' than in 'management', at both 3 and 6 months, indicating a potential for improvement in clinical practice for these dimensions. Conclusion: This study provides a brief patient‐derived questionnaire, expressed with a score with good psychometric performance that can be used for monitoring during intravitreal injection treatment of nAMD patients.